Occurrence and involvement of adenylate cyclase activity in the first step of tobacco mosaic virus infection of Nicotiana tabacum cv Xanthi nc leaves - Abad, P.; Guibbolini, M.; Poupet, A.; Lahlou, B. (Biochimica et biophysica acta, 1986)
Adenylate cyclase activity and its involvement in a physiopathological process (virus infection) were observed in a higher plant, Nicotiana tabacum cv Xanthi nc. The enzyme was characterized in leaves by measuring the conversion of [α- 32P]ATP into cyclic [α- 32P]AMP using a cell membrane preparation. The basal enzyme activity was 1–2 pmol/min per mg protein, was linear with time and protein concentration, and had a temperature optimum between 20 and 25% C. The K m for ATP was 2 mM in the presence or absence of stimulators. GTP (10 −7 M) increased both basal and sodium fluoride-stimulated activities. During the hypersensitive reaction which follows tobacco mosaic virus (TMV) infection, we detected in the first 10 min a 40–80% increase in the basal activity. These results indicate that cAMP could play an important role by mediating the viral and plant host-cell interaction. The rapid pulse-release of cAMP leads us to propose that this nucleotide may, as in animal tissues, represent a secondary messenger in higher plants.